PERMIAN-TRIASSIC CONCHOSTRACAN FAUNAS FROM THE NORTH OF CENTRAL SIBERIA - Orlova E.F. (My University, 1999)
Eight conchostracan faunas described in the paper successively replace one another in the Upper Permian-Middle Triassic sedimentary sequence of the Siberian platform, Taimyr, and Verkhoyansk Range. Data on microsculpture of conchostracan shells are obtained using the scanning electron microscopy (SEM).
Keywords: Triassic; Permian; Paleozoic::Permian; Mesozoic::Triassic; Мезозой::Триасовая; Палеозой::Пермская